La politique des droits des réfugiés colombiens en Équateur : des discours aux pratiques des acteurs de l’aide - Lucie Laplace (Cahiers des Amériques Latines)
This article analyses the evolution of the discourse and practices of aid actors (the State, the UN Refugee Agency, NGOs and local associations) in favor of Colombian refugees in Ecuador from 2007 to 2013. A paradigm of refugees’ rights emerges through innovative constitutional principles (Buen Vivir, Universal Citizenship, and Human Mobility) that come to redefine the boundaries between foreigner and citizen. Dominant in the twentieth century, the security and control approach prevails through discriminatory practices within civil society, and determines the Ecuadorian-Colombian bilateral relations. The deployment of state institutions and the involvement of civil aid stakeholders promote the inclusion of refugees, implementing more effectively their rights. However the most vulnerable populations continue to live in very precarious situations, even if some have refugee status and are assisted by NGOs and local associations.